Valid olfactory impairment tests can help identify mild cognitive impairment: an updated meta-analysis - Zhou, Chunyi; Yang, Chongming; Ai, Yating; Fang, Xueling; Zhang, Ailin; Wang, Yuncui; Hu, Hui (Frontiers in Aging Neuroscience, 2024)
Background: Olfactory testing is emerging as a potentially effective screening method for identifying mild cognitive impairment in the elderly population. Objective: Olfactory impairment is comorbid with mild cognitive impairment (MCI) in older adults but not well-documented in subdomains of either olfactory and subtypes of cognitive impairments in older adults. This metaanalysis was aimed to synthesize the differentiated relationships with updated studies. Methods: A systematic search was conducted in 7 databases from their availability to April 2023. A total of 38 publications were included, including 3828 MCI patients and 8160 healthy older adults. Two investigators independently performed the literature review, quality assessment, and data extraction.The meta-analyses were conducted with Stata to estimate the average effects and causes of the heterogeneity. Results: Compared to normal adults, MCI patients had severe impairment in olfactory function and severe deficits in specific domains of odor identification and discrimination. Olfactory impairment was more severe in patients with Amnestic mild cognitive impairment than in patients with non-amnestic MCI. Diverse test instruments of olfactory function caused large heterogeneity in effect sizes. Conclusion: Valid olfactory tests can be complementary tools for accurate screening of MCI in older adults.